A Case of Neurotrophic Keratopathy Associated with Nasopharyngeal Carcinoma - Sato, Tomoko (Case Rep Ophthalmol, 2018)
PURPOSE: To report a case of neurotrophic keratopathy associated with nasopharyngeal carcinoma. CASE REPORT: A 59-year-old man who had been diagnosed with a nasopharyngeal carcinoma was referred to the authors because of visual disturbance and pain in his right eye. Slit-lamp examination revealed a corneal epithelial defect and corneal stromal edema surrounding the epithelial defect area in his right eye. Magnetic resonance imaging showed a mass in his cavernous sinus, which was identified as nasopharyngeal carcinoma (NPC). We diagnosed neurotrophic keratopathy associated with NPC and initiated treatment with preservative-free artificial tears, antibiotic eye drops, fibronectin, a therapeutic contact lens, and amniotic membrane transplantation. However, the persistent corneal epithelial defect was unresponsive to these treatments. CONCLUSION: Neurotrophic keratopathy secondary to NPC is thought to be rare. We presented a case of neurotrophic keratopathy associated with cavernous sinus metastasis of an NPC. The development of new and more effective treatments for this refractory disease is anticipated.